A retrospective chart review of pirfenidone-treated patients in Sweden: the REPRIS study. Issue 1 (1st January 2016) - Sköld, Carl Magnus; Janson, Christer; Elf, Åsa Klackenberg; Fiaschi, Marie; Wiklund, Kerstin; Persson, Hans Lennart
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive lung disease that usually results in respiratory failure and death. Pirfenidone was approved as the first licensed therapy for IPF in Europe based on phase III trials where patients with a forced vital capacity (FVC) >50% of predicted were included. The aim of this study was to characterise patients treated with pirfenidone in Swedish clinical practice and to describe the adherence to the reimbursement restriction since reimbursement was only applied for patients with FVC below 80% of predicted. Methods: This was a retrospective, observational chart review of IPF patients treated with pirfenidone from three Swedish university clinics. Patients initiated on treatment during the period 28 June 2012 to 20 November 2014 were included. Data on patient characteristics, basis of diagnosis, treatment duration, quality of life, and adverse drug reactions (ADRs) were collected from medical charts. Results: Forty-four patients were screened and 33 were included in the study. The mean treatment duration from start of pirfenidone until discontinuation or end of study was 38 weeks. At the initiation of pirfenidone treatment, FVC was 62.7% (12.1) [mean (SD)], diffusion capacity (DLco) was 45.1% (13.8) of predicted, and the ratio of forced expiratory volume on 1 sec (FEV1) to FVC was 0.78 (0.1). The percentage of patients with an FVC between 50 and 80% was 87%. Ten of the patients had ADRs including gastrointestinal and skin-related events, cough and signs of impaired hepatic function, but this led to treatment discontinuation in only two patients. Conclusion: Data from this chart review showed that adherence to the Swedish reimbursement restriction was followed in the majority of patients during the study period. At the start of pirfenidone treatment, lung function, measured as FVC, was lower in the present cohort of Swedish IPF patients compared with other registry and real-life data. About a third of the patients had ADRs, but discontinuation of the treatment because of ADRs was relatively uncommon.